(untitled) (Indian Journal of Public Health Research & Development, 2020)
Context: Sidoarjo District is one of the districts in East Java Province, Indonesia which has an increase in the number of people aged 60 years and over each year. The achievement of health service performance indicators for residents aged 60 years and over in Sidoarjo District has not reached the standard of 60.31% of the target of 100%. Based on the results of the interviews, information was obtained that the target had not been achieved due to individual internal factors. The purpose of this study was to analyze the influence of predisposing factors of elderly individuals on the utilization of elderly health services held by the Sidoarjo district health centre. This type of research is analaitic observational and cross sectional. The population in this study were elderly people in Sidoarjo District. The sampling technique is proportional stratified random sampling so that the sample is 200 people. Data analysis using statistical tests of the influence of the dependent and independent variables. The results showed that the predisposing factors of the elderly who influenced the utilization of Integrated Services Post for elderly were age (p = 0.029) and gender (p = 0.000). The predisposing factors for the elderly that influence the utilization of Community Health Centre services are Spatial Factors (p = 0,000). The older the age increases the higher the utilization of the elderly Integrated Services Post for elderly. The utilization of Integrated Services Post for elderly services for elderly men is lower than for women. Elderly people who live in rural areas use health centres more than the elderly in urban areas. The recommendation of this study is that health centre needs to give education about the importance of medical examinations at older age can be done since the pre-elderly age. Integrated Services Post for elderly cadres can persuade elderly women to invite their husbands to take medical examinations. Elderly in addition to rural areas, namely urban and small urban areas, they need to get socialization regarding elderly health care programs in health centres to increase the interest of small urban and urban seniors to health centres.